Determination of Attributes in Cotton (Gossypium hirsutum L.) Genotypes in Corn-Soybean Rotation Associated with Acid Amended Soils in the Colombian Eastern Plains - Campuzano Duque, Luis Fernando; Caicedo Guerrero, Samuel; Guevara Agudelo, Judith (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2018)
For the last 15 years, Colombia has developed a research process leading to the expansion of its agricultural frontier at the flat well drained savannas of the Eastern Plains, by improving predominantly acid soils with liming to increase base saturation with depth, vertical liming —as its referred locally—, crop rotation with rice, corn, soybeans, and with the potential to include other crops like cotton in the rotation system. To achieve this, a pioneering research in Colombia was conducted to determine the adaptation of cotton in the acid conditions of the high plains improved sheets. An Agronomic evaluation test was developed using five elite genotypes of cotton in a design of a randomized complete block at four locations in soils with base saturation above 80 %. The results identified a genotype (LC-156), which presented an adaptation to the high plains, associated with an average yield of 2.2 t/ha of cottonseed, 1.5 t/ha of cotton fiber type medium-long, a percentage of fiber extraction above 36.0 %. The comparative advantage of this region for sustainable cotton production is given by the yield of cotton fiber —which ishigher than the national average—, to the 33.2 % reduction in production costs, the quality of long/medium-fiber destined for export and the absence of the pest insect of greatest economic impact in Colombia: the weevil (Anthonomus grandis Boheman).